Features of management and treatment of elderly patients with type 2 diabetes mellitus - L. Yu. Morgunov; E. V. Zemskova (Лечащий Врач)
Type 2 diabetes is a serious burden on the health of the elderly, affecting approximately 25% of people over 65 years of age. It is expected that this percentage will increase sharply in the next decades due to the increase in life expectancy of the population. Diagnostic criteria for diabetes mellitus in elderly patients do not differ from the general population, there are several features of their management. The elderly population varies greatly in functional and cognitive abilities. These factors, along with an increased risk of hypoglycemia, falls and concomitant diseases, complicate the development of treatment regimens, therefore it is necessary to use a personality-oriented approach, minimizing the risk of excessive or insufficient therapy of diabetes, since the use of antidiabetic drugs in the elderly is associated with significant risk. The prevalence of diabetes mellitus significantly increases after the age of 80 with insufficient physical activity, alcohol consumption, a history of cardiovascular diseases, visceral obesity and hypertension. Cognitive impairment is 2 times more common in elderly people with diabetes. In addition to micro- and macrovascular lesions, a complication of diabetes in the elderly is also sarcopenia, which has a negative impact on the physical and psychosocial health of patients with diabetes and worsens their quality of life. Age-related metabolic changes and emerging kidney pathology predispose elderly people to an increased risk of developing diabetes mellitus and diabetic nephropathy, respectively. Despite the available therapy, a significant number of elderly patients with diabetic nephropathy have progressive renal failure and adverse cardiac outcomes, therefore, research is needed to study methods for early detection of diabetic nephropathy and new therapeutic interventions. Among the elderly with diabetes, individuals with poor glycemic control are at higher risk of cardiovascular events. Elderly patients have greater variability in glycemia and are more prone to arrhythmias, but active glucose control can reduce the risk of severe arrhythmia. Treatment of diabetes in elderly patients with heart failure can be a difficult task, taking into account numerous concomitant diseases, primarily chronic kidney disease. The complexity of treatment regimens, the clinical characteristics of patients and the ability of heart failure therapy to influence glucose metabolism and, conversely, the potential of some antidiabetic agents to modulate its outcomes are problems that need to be solved within the framework of an individual approach. Elderly men suffering from diabetes, for the prevention and treatment of osteoporosis, smoking cessation, glycemic control, regular exercise, active prevention and treatment of complications of osteoporosis, as well as testosterone replacement therapy are necessary. In elderly people, it is necessary to use individual pharmacotherapy with hypoglycemic drugs with a low risk of hypoglycemia and proven safety for the cardiovascular system, avoiding excessive treatment and simplifying therapy regimens. Glycemic targets in the elderly as part of individual treatment may be revised. Intensive treatment of elderly people with diabetes is common, creating an increased risk of adverse events such as hypoglycemia and hospitalization due to medication errors. Those receiving many drugs belong to the older age group, have numerous diseases, including kidney failure and dementia. In such patients, it is permissible to de-intensify therapy or even completely cancel hypoglycemic drugs without significantly worsening their glycemic control.